(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The author investigates origins and the essence of the term "community", analyzing sociological and socio-psychological community theories. The researches that she did were distinct different types of the community and analyze its structural components. In the article are also provided results of a qualitative research of the psychological aspects of mental health and counseling professional community.